Participatory Market Chain Approach in Quality Fish Seeds Dissemination Process in Nepal - Gurung, Shailesh; Pokharel, Vishwa C.; Devkota, Chandra Kanta (International Journal of Applied Sciences and Biotechnology, 2016)
Quality fish seeds production and dissemination is found quite lacking part in boosting up the production of aquaculture in Nepal since long decades. Commercialization in fish farming cannot jumped ahead in absence of available inputs and fish seeds are realized a great factor for subsistence to commercialization of fish farming activities. Participatory Market Chain Approach is found to be a key tool for the social and economic upliftment of farmers and different market actors in a common platform with a dynamic solution in a jointly supply chain modality. Limited and monopoly market of inputs supplier hinders the resilience of fishery sector both qualitatively and quantitatively in Nepal. It is extremely realized that the pocket level fish thematic group concept would be very fruitful in ensuring a milestone by representating village and cluster level problem solving arena among different actors, stakeholders and lead farmers for accession of quality inputs by mutual trust building environment covering wider area in a participatory way which will ensure supply chain of quality products, livelihood and income as well. Int J Appl Sci Biotechnol, Vol 4(3): 391-396